2016
DOI: 10.1038/nmat4590
|View full text |Cite
|
Sign up to set email alerts
|

Engineered hybrid cardiac patches with multifunctional electronics for online monitoring and regulation of tissue function

Abstract: In cardiac tissue engineering approaches to treat myocardial infarction, cardiac cells are seeded within three-dimensional porous scaffolds to create functional cardiac patches. However, current cardiac patches do not allow for online monitoring and reporting of engineered-tissue performance, and do not interfere to deliver signals for patch activation or to enable its integration with the host. Here, we report an engineered cardiac patch that integrates cardiac cells with flexible, free-standing electronics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
340
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(347 citation statements)
references
References 44 publications
3
340
0
4
Order By: Relevance
“…For example, noradrenaline release near the cardiac layers may increase the contraction rate of the tissue. Recently our group has shown the ability to trigger the release of drugs by built-in layers of electronics (39). Integration of such a system as an additional layer within the engineered patch could provide on-demand spatiotemporal release of the different biofactors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, noradrenaline release near the cardiac layers may increase the contraction rate of the tissue. Recently our group has shown the ability to trigger the release of drugs by built-in layers of electronics (39). Integration of such a system as an additional layer within the engineered patch could provide on-demand spatiotemporal release of the different biofactors.…”
Section: Resultsmentioning
confidence: 99%
“…Wireless sensing devices enable users to monitor and record their physiological data in real time [1][2][3] . Recently, artificial electronic skin (E-skin) that can simultaneously detect subtle pressure changes, the humidity, and the temperature has been intensively studied for its potential use in various applications, including health monitoring systems, medical diagnostics, soft robotics, and human-machine interfaces [4][5][6][7] . It has been demonstrated that flexible electronic devices and systems can be integrated with the human body or E-skin in the form of implantable, stick-on, or wearable electronics 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Some recent nanotechnology progresses in the field have even added new levels of functionality beyond regeneration, such as status monitor and active control of implanted constructs, [27][28][29] as will be further discussed later in this review.…”
Section: Nanocomposite Bioinks For Te Strategiesmentioning
confidence: 99%
“…28,29,63 Independently of the final application, instrumented microphysiological devices, which are also known as organs-onchips, aim at real-time tracking and online monitoring and reporting of the engineered tissue performance without interfering with the signal reading on being implanted within the host.…”
Section: Integration Of Sensors In Te Systemsmentioning
confidence: 99%